Applying Information Security Risk Management Standards Process for Automated Vehicles - Shatnawi, Malak M. (Bánki Közlemények, 2019)
Development of the transportation system is the main concern for each country, it provides a continual flow of goods, services and information’s essential for the economic, security, safety, welfare, and to the health of its citizens. Transportation generally framed as a key component for progress, the sustainability dimensions represented by the social, economic, and environmental pillars have direct impacts on the cities and regions growth and prosperity which become the main challenge for all researchers and engineers because of the expansion of transportation networks. The rapid modern technology brought changes in all fields including road transportation and infrastructure and one of the most contemporary research subjects in transportation is the Automated Vehicles AV or Self Driven Vehicles SDV. The main challenges in the field of autonomous vehicles rest in the fact of improving road safety, minimizing accidents and human errors. It is known that road safety is a difficult issue including several fields to study such as human, vehicles, roads and socio-economic and environment factors. This paper will focus in transportation, infrastructure and mobility risk management which seeks to make transportation system more efficient in term of safety, security, traffic accidents, security of data and information technology as well as software systems against malfunctions and all kinds of attacks. The aim of the paper is to discuss the challenges and threats faced in the development of the autonomous vehicles AV by studding information security risk management standard process, and explaining how applying the process of International Organization for Standardization (ISO), the concept of applying ISO 27005, to AV will be discussed here through certain processes. Keywords: autonomous vehicles, Information security risk management, transportation, safety and security.